Oxygen evolution electrode with self-supporting structure as well as preparation method and application of oxygen evolution electrode
By rapidly adhering and growing metal oxide nanoparticles on foam metal matrix, the catalyst preparation process is simplified and catalytic activity is improved, the problems of complex preparation processes and scarce resources in the prior art are solved, and efficient catalysts suitable for industrial applications are realized.
Patent Information
- Application Number
- CN202510145689.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-10
AI Technical Summary
The preparation process of existing transition metal oxide catalysts is complex and difficult to achieve large-scale industrial application. The resources of precious metal catalysts are scarce and costly.
Using a self-supported structural electrode, the preparation process is simplified and catalytic activity is improved by rapidly adhering and growing metal oxide nanoparticles on the foam metal matrix. The method includes impregnating the foam metal in an ethanol solution of metal cations and ignition and burning process to allow metal oxide nanoparticles to adhere and grow on the foam metal skeleton.
It has achieved a self-supported structure oxygen precipitation electrode with simple process, low raw material cost, high catalytic activity and suitable for large-scale preparation, overcomes the problems of complex preparation processes and scarce resources in the existing technology, and has the potential to promote the industrialization of OER catalysts.
Smart Images

Figure CN119571360A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a self-supporting oxygen evolution catalyst and a preparation method and application thereof, belonging to the technical field of electrocatalysis. Background Art
[0002] Oxygen evolution reaction (OER) is a crucial step in the process of hydrogen production by water electrolysis, and its slow kinetics limit the efficiency of the overall reaction. In order to improve the efficiency of water electrolysis, the development of efficient OER catalysts has become a research focus. At present, Ir-based and Ru-based noble metals and their oxides are considered to be excellent OER catalysts, but the scarcity and high price of these noble metals limit their feasibility in large-scale industrial applications. Therefore, the development of low-cost and resource-rich non-noble metal catalysts has become a hot topic in current research.
[0003] Among the many non-precious metal catalysts, transition metal oxides have attracted extensive attention due to their excellent catalytic activity and stability. This type of catalyst not only exhibits activity close to that of precious metal catalysts in OER reactions, but also has good long-term stability. However, existing transition metal oxide catalysts are usually obtained through complex preparation processes such as co-precipitation, hydrothermal or electrodeposition, which require strict experimental conditions and equipment control, limiting their application in large-scale industrial production.
[0004] To overcome these problems, researchers have begun to focus on the application of self-supporting electrodes in OER catalysis in recent years. Compared with traditional supported electrodes, self-supporting electrodes can not only significantly improve the performance of catalysts, but also simplify the preparation process. By directly loading metal oxide catalysts on conductive substrates, self-supporting electrodes do not require binders or additional current collectors, which reduces interfacial resistance and improves charge transfer efficiency, thereby accelerating the OER reaction kinetics.
[0005] In addition, the design of the self-supporting structure helps to optimize the specific surface area and pore structure of the electrode, increase the contact area between the catalyst and the electrolyte, and further promote the OER reaction. This structure not only improves the utilization efficiency of the catalyst, but also enhances its mechanical stability, effectively preventing the catalyst from falling off or losing during long-term electrolysis. Therefore, the self-supporting metal oxide electrode exhibits excellent electrocatalytic performance and long-term durability, showing a wide range of application prospects. Summary of the invention
[0006] The present invention optimizes the composition and preparation process of the metal oxide catalyst by introducing a self-supporting structure, further improving the electrocatalytic water oxidation performance of the catalyst. The method is simple, economical and environmentally friendly, suitable for practical application in large-scale hydrogen production, and has the potential to promote the industrial development of OER catalysts.
[0007] The present invention aims to solve the shortcomings of the prior art that the preparation process of the self-supporting metal oxide electrode is complicated and difficult to apply on a large scale. The present invention provides a method for making metal oxide nanoparticles quickly adhere to and grow on the foam metal skeleton by immersing the foam metal in an ethanol solution of metal cations and igniting and burning the foam metal. The method has the advantages of simple process, low raw material cost, high catalytic activity, excellent selectivity, and suitability for large-scale preparation, and is expected to provide an efficient catalyst for the industrialization of hydrogen production by electrolysis of water.
[0008] According to one aspect of the present application, a self-supporting oxygen evolution electrode is provided. The self-supporting oxygen evolution electrode comprises a substrate and a porous catalytic layer supported on a surface of the substrate.
[0009] The porous catalytic layer is composed of metal oxide nanoparticles.
[0010] The metal oxide is selected from at least one of oxides of Ni, Fe, Co, Mn, Ce, W, V, and Mo.
[0011] In the self-supporting oxygen evolution electrode, the loading amount of the metal oxide is 0.1-100 mg / cm 2 .
[0012] The particle size of the metal oxide nanoparticles is 10-30 nm.
[0013] The thickness of the porous catalytic layer is 50-300 nm.
[0014] The thickness of the substrate is 0.1-5 mm.
[0015] The substrate is selected from at least one of foamed nickel, foamed copper, foamed iron or foamed iron-nickel alloy.
[0016] According to another aspect of the present application, a method for preparing the above-mentioned self-supporting structure oxygen precipitation electrode is provided, comprising the following steps: The substrate is immersed in an ethanol solution containing a metal salt, the substrate is taken out, and ignited to obtain the self-supporting structure oxygen precipitation electrode.
[0017] The metal salt is selected from at least one of nickel nitrate, iron nitrate, cobalt nitrate, manganese nitrate, cerium nitrate, tungsten chloride, vanadium chloride and molybdenum chloride.
[0018] The concentration of the ethanol solution containing the metal salt is 0.01-1 mol / L.
[0019] The immersion time is 1 to 60 minutes.
[0020] The ignition atmosphere is an oxygen atmosphere or an air atmosphere.
[0021] The obtained substrate is cleaned.
[0022] The cleaning is performed by sequentially using hydrochloric acid, ethanol and water.
[0023] When the self-supporting structure oxygen evolution electrode contains multiple metal oxides, the preparation method thereof comprises the following steps: The substrate is immersed in an ethanol solution containing a first metal salt, the substrate is taken out, ignited, and then immersed in an ethanol solution containing a second metal salt, the substrate is taken out, ignited, and so on.
[0024] The further specific steps are: Step 1) Cut the foam metal substrate into 10×10 cm 2 The blocks were ultrasonically cleaned with 1-3 mol / L hydrochloric acid solution for 30 minutes, and then repeatedly cleaned with ethanol and deionized water.
[0025] Step 2) Dissolve the metal salt in an ethanol solution. After the metal salt is completely dissolved, soak the treated foam metal substrate in the above solution for 5 minutes. After the reaction is completed, take out the foam metal substrate and ignite and burn it under ambient conditions. After the substrate is cooled, wash it with deionized water and ethanol, and then dry it in an oven at 60 ° C overnight to obtain a self-supporting metal oxide catalyst.
[0026] Study on electrocatalytic water oxidation performance: In a standard three-electrode electrolytic cell system, the prepared metal oxide catalyst was used as the working electrode, the Hg / HgO electrode and the carbon rod were used as the reference electrode and the counter electrode, respectively, and the electrolyte was 1M KOH solution. All electrochemical performance tests were performed using the Chenhua 760E electrochemical workstation. Before the test, cyclic voltammetry (CV) electrochemical activation was performed, and the voltage range was set to 0-1.5 V (vs. Hg / HgO), the scan rate was 100 mV / s, and the number of scans was 40. After the CV scan curve was stable, the linear sweep voltammetry (LSV) polarization curve test was performed, and the potential range was set to 0-1.5V (vs. Hg / HgO), the scan rate was 10 mV / s, and iR compensation was performed, and the compensation value was set to 85%. Finally, the stability of the catalyst was evaluated by constant potential method.
[0027] According to another aspect of the present application, there is provided an application of the above-mentioned self-supporting structure oxygen evolution electrode for alkaline oxygen evolution reaction.
[0028] The key to the present invention lies in the precise selection of metal salts and solvents. First, compared with other metal salts, metal nitrates have unique combustion-supporting properties and are easily decomposed and release oxidizing gases under high temperature conditions. This not only increases the temperature during the burning process, but also reduces the need to convert metal salts from ionic states to solid states through steps such as roasting in the traditional preparation process. In addition, anhydrous ethanol, as a solvent, exhibits good solubility for metal nitrates and chlorides, and its solubility is significantly stronger than other common alcohol solutions. This provides a guarantee for the uniformity of the reaction. The flammability of ethanol further simplifies the process flow, and the heat released by combustion can quickly reach the required temperature, thereby facilitating the efficient preparation of the metal oxide layer. Compared with the liquid phase ion exchange strategy in the existing patent, although this method can prepare self-supporting structure electrodes, its process usually requires a long immersion time, and the loading amount of the catalyst active component is still limited. The present invention achieves a more efficient metal oxide preparation path by optimizing the metal salt and solvent system, overcoming the bottleneck in the prior art.
[0029] The beneficial effects of this application include: Environmental protection: The present invention does not use organic precipitants, thus avoiding environmental pollution; in addition, no strong alkaline precipitants are used, and the high temperature environment generated in the natural process of ethanol is used to make the catalyst particles evenly adhere to the foam metal skeleton, thereby reducing the environmental burden.
[0030] Economy and safety: The method of the present invention does not rely on high temperature and high pressure equipment, is safe to operate and low cost, and is suitable for large-scale scale-up and batch preparation.
[0031] Excellent catalytic performance: The catalyst is loaded on the support in situ, has strong binding force, reduces the risk of catalyst shedding, and has a small contact resistance of the electrode. The prepared oxygen evolution electrode exhibits high catalytic activity and low overpotential, has a small internal resistance, and the catalyst is not easy to fall off, which prolongs the service life of the electrode, and has the advantages of low cost and easy industrial production.
[0032] Advantages of self-supporting electrodes: As a self-supporting electrode, the present invention does not need to use a binder, which improves the electron transport capacity and reduces the interface resistance. The nanostructure of the surface layer provides a rich pore structure and good hydrophilicity, which not only promotes the exposure of active sites, but also improves the permeability of the electrolyte.
[0033] Highly efficient catalytic performance: The iron oxide-tungsten oxide catalyst prepared by the present invention exhibits excellent catalytic activity and stability in the alkaline water oxidation process. The catalyst can achieve 1 A / cm in 1 mol / L KOH solution at a potential of only 1.65-1.75 V (vs. RHE). 2 industrial current density, and is capable of 0.5 A / cm 2 It maintains stability for more than 1000 hours at a current density that meets commercial requirements and provides a reliable catalyst for the development of water electrolysis hydrogen production systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope (SEM) image of the FeO / NF catalyst in Example 1, with a scale of 50 μm.
[0035] Figure 2 This is the SEM image of the FeO-WO / NF catalyst in Example 2, with a scale of 50 μm.
[0036] Figure 3 is a linear sweep voltammetry (LSV) curve of the FeO-WO / NF catalyst in Example 2.
[0037] Figure 4 This is the stability test curve of the FeO-WO / NF catalyst in Example 2. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with the examples. The following examples are non-limiting implementation measures, and are intended to enable those skilled in the art to more fully understand the technical content of the present invention, but are not intended to limit the scope of the present invention in any way.
[0039] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.
[0040] Embodiment 1: The preparation method of the self-supporting structure iron oxide catalyst for oxygen evolution reaction in alkaline environment is as follows: Step 1) Cut the nickel foam substrate into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min and then repeatedly rinsed with ethanol and deionized water to remove the surface oxide layer.
[0041] Step 2) prepare a 0.5 mol / L ferric nitrate ethanol solution; immerse the treated nickel foam in the solution for 5 minutes; after the reaction is completed, take out the nickel foam, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain a self-supporting iron oxide catalyst (named FeO / NF).
[0042] The material morphology was characterized by scanning electron microscopy, and the results showed that the iron oxide catalyst had a granular stacking structure and grew on the skeleton of the nickel foam matrix ( Figure 1 ). In a standard three-electrode electrolytic cell system, the above catalyst was directly used as the working electrode, Hg / HgO and carbon rod were used as the reference electrode and counter electrode respectively, the electrolyte was 1.0 mol / L KOH, and all electrochemical performance tests were performed using a Chenhua 760E electrochemical workstation. Electrochemical tests showed that this type of catalyst requires an anode potential of 1.77 V (vs. RHE) to achieve 1 A / cm 2 Industrial current density.
[0043] Embodiment 2: The preparation method of the self-supporting structure oxide catalyst for oxygen evolution reaction in an alkaline environment mentions that a multi-component metal oxide composite catalyst can be prepared to achieve a better catalytic effect. Here, chloride is used for corresponding research as follows: Step 1) Cut the nickel foam substrate into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min, and then rinsed repeatedly with ethanol and deionized water.
[0044] Step 2) Prepare a 0.5 mol / L ferric nitrate ethanol solution; soak the treated nickel foam in the solution for 5 minutes; after the reaction is completed, take out the nickel foam, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain a self-supporting iron oxide catalyst. Further, soak the obtained iron oxide catalyst in a 0.5 mol / L tungsten chloride ethanol solution for 5 minutes; after the reaction is completed, take out the substrate, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain a self-supporting iron oxide-tungsten oxide catalyst (named FeO-WO / NF). In addition, tungsten chloride is replaced by molybdenum chloride and vanadium chloride, and the catalysts finally obtained are iron oxide-molybdenum oxide (FeO-MoO / NF) and iron oxide-vanadium oxide (FeO-VO / NF).
[0045] In terms of morphology, this secondary calcination process has little effect on the morphology of the catalyst, and it still presents a uniform nanoparticle structure ( Figure 2 ), the catalytic performance of the two catalysts was further evaluated by electrochemical testing in the same way. Compared with the iron oxide catalyst, the performance of the prepared two-component oxide catalyst was improved, and an anode potential of 1.69 V (vs. RHE) was required to achieve 1 A / cm 2 Industrial current density ( Figure 3 ); FeO-WO / NF catalyst at 0.5 A / cm 2 It can operate stably for more than 1000 hours at a current density of Figure 4 ).
[0046] Embodiment 3: The preparation method of the self-supporting structure electrocatalyst for oxygen evolution reaction in alkaline environment mentions that the ratio of the metal salt precursor can be adjusted, and the corresponding research is as follows: Step 1) Cut the nickel foam substrate into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min and then repeatedly rinsed with ethanol and deionized water to remove the surface oxide layer.
[0047] Step 2) Prepare an ethanol solution of 0.5 mol / L ferric nitrate and 0.5 mol / L tungsten chloride; prepare two solutions with different ratios of Ni and W, one containing 1.0 mol / L ferric nitrate and 0.3 mol / L tungsten chloride, and the other containing 0.3 mol / L ferric nitrate and 1.0 mol / L tungsten chloride. Soak the treated nickel foam in the above solutions in turn for 5 minutes; after the reaction is completed, take out the nickel foam, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain three catalysts of self-supporting structures FeO-WO / NF-1, FeO-WO / NF-2 and FeO-WO / NF-3.
[0048] Electrochemical tests showed that the three catalysts exhibited different catalytic activities for oxygen evolution, among which FeO-WO / NF-1 had the best catalytic performance, achieving 1 A / cm at an electrode potential of only 1.69 V (vs. RHE). 2 The other two require 1.72 V (vs. RHE) and 1.74 V (vs. RHE).
[0049] Embodiment 4: The preparation method of the self-supporting structure electrocatalyst for oxygen evolution reaction in an alkaline environment mentions that the concentration of the metal salt in step 2 is 0.01~1.0 mol / L. The corresponding research is as follows: Step 1) Cut the nickel foam substrate into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min and then repeatedly rinsed with ethanol and deionized water to remove the surface oxide layer.
[0050] Step 2) Prepare 0.1, 0.5, and 1.0 mol / L ferric nitrate ethanol solutions respectively. Soak the treated nickel foam in the above solution for 5 minutes; after the reaction is completed, take out the nickel foam, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain FeO / NF catalysts prepared with solutions of different metal salt concentrations.
[0051] In the metal salt solution of step 2, it was found that the prepared solution had limited solubility for metal salts, and excess metal salts were difficult to completely dissolve in ethanol. According to the results of scanning electron microscopy, the morphology of the catalysts showed stacked particles, but the stacked particles were relatively sparse at low concentrations. Therefore, it is more appropriate to control the metal salt concentration of this type of self-supporting structure catalyst to be synthesized at 0.5 mol / L.
[0052] Embodiment 5: The method for preparing a self-supporting electrocatalyst for oxygen evolution reaction in an alkaline environment mentions that the type of metal salt in step 2 can be adjusted, and the corresponding research is as follows: Step 1) Cut the nickel foam substrate into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min and then repeatedly rinsed with ethanol and deionized water to remove the surface oxide layer.
[0053] Step 2) Prepare 0.5 mol / L metal salt ethanol solutions, including iron nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, cerium nitrate, tungsten chloride, vanadium chloride, and molybdenum chloride. Soak the treated nickel foam in the above solution for 5 minutes; after the reaction is completed, take out the nickel foam, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain a metal oxide catalyst prepared with different metal salt solutions.
[0054] According to the results of scanning electron microscopy, the morphology of the catalysts all appeared to be stacked particles without major changes. However, there were large differences in the oxygen evolution activity of the catalysts. Among them, the self-supporting structure catalyst prepared from iron nitrate had the best catalytic activity.
[0055] Embodiment 6: The preparation method of the self-supporting structure electrocatalyst for oxygen evolution reaction in an alkaline environment mentions that the substrate immersion time in step 2 is 1 to 60 minutes, and the corresponding research is as follows: Step 1) Cut the nickel foam substrate into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min and then repeatedly rinsed with ethanol and deionized water to remove the surface oxide layer.
[0056] Step 2) prepare a 0.5 mol / L ferric nitrate ethanol solution; immerse the treated nickel foam in the above mixed solution, and control the immersion time to be 1 minute, 5 minutes, and 60 minutes respectively; after the reaction is completed, take out the nickel foam, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain iron oxide catalysts prepared with different immersion times.
[0057] In terms of morphology, the immersion time in step 2 has little effect on the morphology of the catalyst; in terms of catalytic activity, the activity of the catalyst obtained with a shorter immersion time is reduced, while extending the immersion time has no obvious effect on improving the catalytic activity. Comprehensive analysis shows that the most appropriate substrate immersion time is 5 minutes.
[0058] Embodiment 7: The preparation method of the self-supporting structure electrocatalyst for oxygen evolution reaction in an alkaline environment mentions that the ignition atmosphere in step 2 is a pure oxygen condition or an atmospheric environment, and corresponding research is conducted as follows: Step 1) Cut the nickel foam substrate into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min and then repeatedly rinsed with ethanol and deionized water to remove the surface oxide layer.
[0059] Step 2) prepare a 0.5 mol / L ferric nitrate ethanol solution; immerse the treated nickel foam in the above mixed solution for 5 minutes; after the reaction is completed, take out the nickel foam, ignite and burn it under ambient conditions or pure oxygen conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain an iron oxide catalyst prepared with different ignition environments.
[0060] In terms of morphology, the different ignition environments in step 2 have little effect on the catalyst, but in terms of catalytic activity, the catalyst prepared under pure oxygen conditions shows a slightly increased oxygen evolution catalytic activity.
[0061] Embodiment 8: The preparation method of the self-supporting structure electrocatalyst for oxygen evolution reaction in alkaline environment mentioned that the substrate can be replaced, which can also achieve good results. Here, foam copper and foam iron are selected as the research substrates, as follows: Step 1) Cut the foam copper and foam iron into 10*10 cm 2 The size was ultrasonically cleaned with 2 mol / L hydrochloric acid for 30 min, and then rinsed repeatedly with ethanol and deionized water.
[0062] Step 2) prepare a 0.5 mol / L ferric nitrate ethanol solution; immerse the treated copper foam or iron foam in the solution for 5 minutes; after the reaction is completed, take out the copper foam or iron foam, ignite and burn it under ambient conditions; after cooling, wash it with deionized water and ethanol, and dry it in an oven overnight to obtain a self-supporting iron oxide catalyst.
[0063] In terms of morphology, replacing the matrix with copper foam or iron foam has little effect on the morphology of the catalyst, which still presents a uniform nanoparticle structure. The catalytic performance of the two catalysts was further evaluated through electrochemical tests in the same way. Compared with the nickel foam as the matrix, the performance of both catalysts was reduced, among which the catalyst with iron foam as the base had relatively outstanding performance.
[0064] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An oxygen evolution electrode of a self-supporting structure, characterized in that: The self-supporting oxygen evolution electrode comprises a substrate and a porous catalytic layer supported on the surface of the substrate; The porous catalytic layer is composed of metal oxide nanoparticles; The metal oxide is selected from at least one of oxides of Ni, Fe, Co, Mn, Ce, W, V, and Mo; In the self-supporting oxygen evolution electrode, the loading amount of the metal oxide is 0.1-100 mg / cm 2 ; The particle size of the metal oxide nanoparticles is 10-30 nm; The thickness of the porous catalytic layer is 50-300 nm; The thickness of the substrate is 0.1-5 mm.
2. The oxygen evolution electrode of the self-supporting structure according to claim 1, characterized in that: The substrate is selected from at least one of foamed nickel, foamed copper, foamed iron or foamed iron-nickel alloy.
3. A method for preparing a self-supporting oxygen precipitation electrode according to any one of claims 1 or 2, characterized in that: The following steps are involved: The substrate is immersed in an ethanol solution containing a metal salt, the substrate is taken out, and ignited to obtain the self-supporting structure oxygen precipitation electrode.
4. The preparation method according to claim 3, characterized in that: The metal salt is selected from at least one of nickel nitrate, iron nitrate, cobalt nitrate, manganese nitrate, cerium nitrate, tungsten chloride, vanadium chloride and molybdenum chloride; The concentration of the ethanol solution containing the metal salt is 0.01-1 mol / L.
5. The preparation method according to claim 3, characterized in that: The immersion time is 1 to 60 minutes; The ignition atmosphere is an oxygen atmosphere or an air atmosphere.
6. The preparation method according to claim 3, characterized in that: The obtained substrate is cleaned; The cleaning is performed by sequentially using hydrochloric acid, ethanol and water.
7. The preparation method according to claim 3, characterized in that: When the self-supporting structure oxygen evolution electrode contains multiple metal oxides, the preparation method thereof comprises the following steps: The substrate is immersed in an ethanol solution containing a first metal salt, the substrate is taken out, ignited, and then immersed in an ethanol solution containing a second metal salt, the substrate is taken out, ignited, and so on.
8. An application of the oxygen evolution electrode of the self-supporting structure according to claim 1, characterized in that: Used for alkaline oxygen evolution reaction.
Citation Information
Patent Citations
Preparation method of three-dimensional ferrocobalt metal oxide oxygen evolution catalyst
CN119307955A
Method of preparation of electrode for electrocatalysis
US20230250538A1